Contribution to the Thermal Renovation of Old Buildings: Numerical and Experimental Approach for Characterizing a Double Window. (November 2015) - Mankibi, Mohamed El; Cantin, Richard; Zoubir, Amine
Abstract: In a global context of climate change and greenhouse gas emissions, the construction sector has a great potential for energy savings and environmental impact reduction. Nearly two-thirds of French buildings were built without any existing thermal regulation: thermal renovation of these buildings is a priority. However, some of these buildings are classified as "historical heritage remarkable architecture"; this strong constraint does not allow the use of traditional renovation methods. This study aims to characterize the thermal behavior of a double window. A numerical thermal model is developed taking into account the heat and mass transfer in the double window. A specific experimental platform has also been designed and built to experimentally characterize the behavior of the double window and to validate the developed numerical model. A simulation protocol was then defined and implemented in order to outline the key parameters and therefore make recommendations for double window implementation and their design. The numerical and experimental results were used to characterize the influence of the thickness of the air gap of the double window, the thermal inertia of the facade and the ventilation strategies.